Performance of F4 arabic coffee progenies before and after framework pruning - Carvalho, Gladyston Rodrigues; Botelho, Cesar Elias; Rezende, Juliana Costa de; Ferreira, Andre Dominguett; Cunha, Rodrigo Luz da; Pedro, Francisco Carlos (Coffee Science - ISSN 1984-3909, 2013)
The use of densification in coffee plantations is one of the factors of increased productivity; however, there is theneed to select genotypes adapted to this system of planting. The objective of this study was to select progenies from the cross between the Catuaí Amarelo IAC 2077-1-2-12-70 and Mundo Novo IAC 515-20 with good agronomic characteristics beforeand after framework pruning (cutting off all plagiotropic branches at 20-30 cm from the orthotropic branch). The experiment was conducted at the Experimental Farm of Epamig in the municipality of Tres Pontas, MG , in 1996 , and after evaluating eight harvests the trees underwent pruning. 39 progenies and three cultivars, IAC 99, Rubi MG 1192, Acaiá Cerrado MG 1474,were used as controls, with evaluations for productivity characteristics ( before and after pruning ), bean yield , percentage offruits with empty locule, grain types such as flat and oval and grains with a high screen size , length and number of nodes inplagiotrophycal branch and length of the orthotropic bud, after pruning the plants. The genotype 1189-12-52-2 was the most productive before and after framework pruning. The higher yields were presented by genotypes 1189-9-80-3, 1190-2-16-1 and Acaiá Cerrado MG 1474. There were, in all studied coffee trees, low percentages of empty locule and oval fruit, presenting a high percentage of beans with a screen size of 16 and above. The genotypes studied showed satisfactory response to pruning.